Studi analisis kepribadian paradigma Milon dengan penyesuaian perkawinan pada pasutri dengan masa pernikahan 10 tahun - Nur Rakhmanto Heryana; Zahra Naila Husnayain (THE JOURNAL OF Mother and Child Health Concerns, 2023)
Background: One of the problems in marriage is due to the lack of interaction between partners. Each personality type influences this interaction. Purpose: This study aims to determine the effect of Millon's personality type on marital adjustment. The subjects of this study were five married couples with a marriage age of 10 years and over. The technique used in this study is a non-probability sampling technique, namely purposive sampling. Methods: The method for measuring marital adjustment, this study used the Dyadic Adjustment Scale (DAS), while to measure individual personality types, this study used the Millon Clinical Multiaxial Inventory-IV (MCMI-IV). MCMI-IV is a measurement tool that can represent a person's personality type. MCMI-IV Guidelines Invalid 1. Scale V > 1, 2. Scale W > 19, Scale X < 7 and > 114, Scale 1-8B (All) < 60 (BR). to test the research hypothesis using MCMI-IV and DAS software. Result: The result is that there is an influence of personality type on marital adjustment. Conclusion: Certain personality types correlate with patterns of marital adjustment between partners.   Keywords: Millon Personality; Personality Type; Marital Adjusment; Theodore Millon; Divoce Rate.   Pendahuluan: Salah satu masalah dalam pernikahan adalah karena kurangnya interaksi antar pasangan. Tipe kepribadian masing-masing mempengaruhi interaksi ini. Tujuan: Untuk mengetahui pengaruh tipe kepribadian Millon terhadap penyesuaian perkawinan. Subyek penelitian ini adalah lima pasangan suami istri dengan usia pernikahan 10 tahun keatas. Teknik yang digunakan dalam penelitian ini adalah teknik non-probability sampling yaitu purposive sampling. Metode: Penelitian ini menggunakan metode Dyadic Adjustment Scale (DAS), sedangkan untuk mengukur tipe kepribadian individu, penelitian ini menggunakan Millon Clinical Multiaxial Inventory-IV (MCMI-IV). MCMI-IV merupakan alat ukur yang dapat mewakili tipe kepribadian seseorang. Pedoman MCMI-IV Tidak Valid 1. Skala V > 1, 2. Skala W > 19, Skala X < 7 dan > 114, Skala 1-8B (Semua) < 60 (BR). Untuk menguji hipotesis penelitian menggunakan software MCMI-IV dan DAS. Hasil: Terdapat pengaruh tipe kepribadian dengan penyesuaian perkawinan. Simpulan: Tipe kepribadian tertentu berkorelasi dengan pola penyesuaian perkawinan antara pasangan.